1999
DOI: 10.1007/s004670050589
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin type 2 receptor is important in the normal development of the ureter

Abstract: In humans, the actions of angiotensin II are transduced through the AT1 and AT2 receptors which have recently been implicated in renal organogenesis. Polymorphisms in the human angiotensin II receptor genes have been linked to cardiovascular and nephrological disorders. In this study we evaluated 35 patients with either primary obstructive megaureter or posterior urethral valves. Each was genotyped for the A1166 AT1 polymorphism and the recently described A-1332G AT2 transition. The incidence of these genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
29
1
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 26 publications
4
29
1
2
Order By: Relevance
“…A lower frequency of G allele in males with ureteral obstruction was found in our population. On the contrary, previous studies showed a significantly higher frequency in Caucasian males with UPJO or UVJO (7,9), whereas another study in Japanese males showed no difference (10). The discrepancy among these studies is more likely to be the result of the limited number of included patients because the genetic background, at least among Caucasians, does not differ.…”
contrasting
confidence: 46%
See 2 more Smart Citations
“…A lower frequency of G allele in males with ureteral obstruction was found in our population. On the contrary, previous studies showed a significantly higher frequency in Caucasian males with UPJO or UVJO (7,9), whereas another study in Japanese males showed no difference (10). The discrepancy among these studies is more likely to be the result of the limited number of included patients because the genetic background, at least among Caucasians, does not differ.…”
contrasting
confidence: 46%
“…In contrast, Yim et al (17) found that this transition occurred significantly less often in Korean patients (males and females) with VUR than in normal controls. Previous studies (9,11), including ours, showed no significant difference in the frequency of the A-G transition in patients with PUV, which is expected because the At2r mRNA expression is absent in the urethral area (7).…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Available data support two mechanistic scenarios on how ectopic c-Ret/GFR␣1 activation might occur: (1) Anterior expansion of the GDNF field (i.e., anterior to the specified metanephric anlagen) as a result of loss of a GDNF repressor, such as Foxc1 or Slit2/Robo2 13,14 ; and (2) increased responsiveness of the duct to GDNF from loss of antagonistic signals, such as Sprouty1 in the WD, 15 or around the duct in the periureteral mesenchyme, such as Bmp4 or Agtr2. 16,17 Both models are accompanied by ectopic GDNFRet activity. Thus, there is clear evidence of control at multiple levels to ensure normal metanephric development.…”
mentioning
confidence: 99%
“…An example is provided by the association of a polymorphism, or common genetic variation, of the angiotensin II type 2 receptor (AT2) gene with a spectrum of disorders including pelviureteric junction obstruction and megaureter (13,16). The genetic variant most likely affects splicing and mRNA transcript levels of this growth factor receptor implicated in cell survival in developing kidney and lower urinary tract (13).…”
mentioning
confidence: 99%